Strategies to include artistic structural elements in the mass public transportation system in Maracaibo, Venezuela (Gaceta Técnica, 2014)
The main objective of this article is to propose strategies for the public art incorporation in the Metro lines of Maracaibo – Venezuela. In order to co-produce the harmony place sense with the urban design practices that shape “marabino” public space morphology. Therefore, on the basis of the international best urban practice analysis and process establishment that carry out the public space production, strategies for including artistic structural elements are proposed to be implemented in mass public transportation system of Maracaibo, using as analysis methodology the incorporation of new ways of conceiving integrated space with art through the relationship among three elements: art, landscape and stations architecture. The result is: a) Fact sheets where integral elements relate to landscape, b) Strategies to include art in future Metro lines of Maracaibo
Keywords: urban mobility; public space; public art; metro